IDENTIFIKASI SENYAWA KIMIA FENOLIK DALAM EKSTRAK ETIL ASETAT KULIT BUAH JENGKOL - Ahmad sopian; Ahmad Darmawan; Partomuan Simanjuntak (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Jengkol (Archidendron pauciflorum (Benth.) I.C Nielsen) is a plant that is already familiar in Indonesia and is widely used as a processed food that is quite popular. One of the underutilized parts of the jengkol plant is the skin. Jengkol fruit peel contains alkaloid compounds, flavonoids, tannins, glycosides, sapoinin and steroids or triterpenoids. The purpose of this study was to determine the content of chemical compounds in ethyl acetate extract of jengkol fruit peel, and to test antioxidant activity by DPPH free radical reduction method.The results of isolation, purification in ethyl acetate extract of jengkol fruit skin does not provide activity as an antioxidant. The results of the analysis using FTIR spectrophotometry, Gas chromatography-Mass Spectrometry (GC-MS) and Nuclear Magnetic Resonance Spectroscopy (1HNMR).Keywords: Antioksidan ,archidendron pauiflorum (Benth) I.C Nielsen, jengkol, (1- (2,6-dihydroxy, 4methoxy phenyl) decane-1-one).